Mapping irrigated areas in the dry zone of Myanmar by differentiating evapotranspiration from irrigated and rain-fed areas [Abstract only] - Douangsavanh, Somphasith; McCartney, Matthew P.; Lacombe, Guillaume (2014)
In the Dry Zone of Myanmar, variability in water resources and insufficient capacity to manage that variability is one of the main causes of food insecurity. Seasonal water scarcity is widely acknowledged to be a key constraint to livelihoods and peoples’ wellbeing. This paper describes analyses conducted as a contribution to a detailed water resource assessment of the Dry Zone of Myanmar, which sought to provide information on current water availability and its use in agriculture. A key unknown is the area of dry season irrigation. The paper describes an attempt to estimate the actual area irrigated during the dry seasons (2011-2012) and to determine effective irrigation volumes by differentiating actual evapotranspiration (ET) in irrigated and rain-fed areas. The results indicate that 256,578 ha were irrigated. This contrasts with the total irrigable area of 344,257 ha as stated by the Irrigation Department (ID), the JICA estimate of 382,110 ha, and the FAO estimate of total irrigated area of 685,246 ha. ET in rain-fed and irrigated areas in conjunction with potential evapotranspiration (PET) were compared between three different areas located in the north, the center and the south of the Dry Zone. Actual water volume utilized by crops is much smaller than the volume of water diverted for irrigation, suggesting significant scope for improving irrigation efficiency.